THE INFLUENCE OF FINANCIAL LITERACY, SELF-CONTROL, AND CONFORMITY ON CONSUMPTIVE BEHAVIOR IN THE USE OF ONLINE FOOD DELIVERY APPLICATIONS - Yulita Yulita; Ati Sumiati; Sri Zulaihati (Nindikayla Institute, 2023)
This study aims to determine the effect of financial literacy, self-control, and conformity partially or simultaneously on consumptive behavior using online food delivery applications in students of the Faculty of Economics, State University of Jakarta. The method used in this study is quantitative. The population of this study was 617 students with 237 students who were used as research samples using simple random sampling technique. Primary data was used as a questionnaire / questionnaire to obtain research data. The results showed that partially the financial literacy variable had a significant adverse effect on consumptive behavior. The self-control variable also has a negative and significant influence on consumptive behavior. While the conformity variable has a positive and significant influence on consumptive behavior. Simultaneously, financial literacy, self-control, and conformity variables influence the consumptive behavior of online food delivery applications in students of the Faculty of Economics, State University of Jakarta. The test results of the coefficient of determination of 44.7%, while other factors outside the study influence the rest. The conclusion that can be drawn from this research is that there is an influence between Financial Literacy, Self-Control, and Conformity on Consumptive Behavior using online food delivery applications in students of the Faculty of Economics, State University of Jakarta